2022
DOI: 10.3390/ijms231810479
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Cellular Mechanisms of Propolis and Its Polyphenolic Compounds against Cancer

Abstract: In recent years, interest in natural products such as alternative sources of pharmaceuticals for numerous chronic diseases, including tumors, has been renewed. Propolis, a natural product collected by honeybees, and polyphenolic/flavonoid propolis-related components modulate all steps of the cancer progression process. Anticancer activity of propolis and its compounds relies on various mechanisms: cell-cycle arrest and attenuation of cancer cells proliferation, reduction in the number of cancer stem cells, ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 419 publications
1
22
0
Order By: Relevance
“…Accumulating evidence suggests that TME, including cancer cells and immune cells, supports tumor growth and evasion (19,20) . Several studies have pointed to the critical task carried out by CD39 in generating this immunosuppressive environment (21,22) .…”
Section: Discussionmentioning
confidence: 99%
“…Accumulating evidence suggests that TME, including cancer cells and immune cells, supports tumor growth and evasion (19,20) . Several studies have pointed to the critical task carried out by CD39 in generating this immunosuppressive environment (21,22) .…”
Section: Discussionmentioning
confidence: 99%
“…Propolis reduces oxidative stress in wounds by inducing the expression of antioxidant related genes (hemeoxygenase-1 (HO-1), glutamate-cysteine ligase- modifier GCLM and- catalytic GCLC subunits) and improves collagen expression and cell viability on cells exposed to high levels of oxidative stress. It was also demonstrated that propolis and some of its active substances have a pronounced cytostatic [ 64 , 65 , 66 , 67 , 68 ] anticarcinogenic and antitumor effect both in in vitro and in vivo tumor models [ 64 , 65 , 66 , 67 , 68 ]. Honeybee propolis and its components (CA, CAPE, artepilin C, quercetin, naringenin, resveratrol, galangin, genistein and other) are the most promising as antitumor and anti-inflammatory agents [ 5 , 57 , 58 , 64 , 65 , 66 , 67 , 68 ].…”
Section: Botanical Sources Of Propolismentioning
confidence: 99%
“…It was also demonstrated that propolis and some of its active substances have a pronounced cytostatic [ 64 , 65 , 66 , 67 , 68 ] anticarcinogenic and antitumor effect both in in vitro and in vivo tumor models [ 64 , 65 , 66 , 67 , 68 ]. Honeybee propolis and its components (CA, CAPE, artepilin C, quercetin, naringenin, resveratrol, galangin, genistein and other) are the most promising as antitumor and anti-inflammatory agents [ 5 , 57 , 58 , 64 , 65 , 66 , 67 , 68 ]. This strategy opens a new venue for cancer prevention to cancer treatment as well as treatment of numerous diseases associated with oxidative stress and inflammation, including allergy diseases.…”
Section: Botanical Sources Of Propolismentioning
confidence: 99%
See 2 more Smart Citations